CONTINUOUS DISPUTES AND FIGHTS ARE THE MOST POPULAR REASONS FOR DIVORCE - Nadia Romadhon; Abdul Rachmad Budiono; Hanif Nur Widhiyanti (CV. RADJA PUBLIKA, 2025)
Marriage is a spiritual and physical bond between a man and a woman to form a family that is peaceful, loving, and merciful. However, not all marriages are harmonious and lasting. Data from the Religious Courts shows that the most common reason for divorce in Indonesia is persistent disputes and quarrels. This study aims to analyze the legal provisions related to these reasons, as stipulated in Article 116 letter (f) of the Compilation of Islamic Law and Article 19 letter (f) of Government Regulation No. 9 of 1975, as well as the implementation and development of their formulation through SEMA Number 3 of 2023. In practice, judges have the freedom to assess whether a household conflict has met the requirements of